Teachers’ Use of Information and Communication Technology (ICT) on English Subject at SMA Negeri 4 Kendari - Astuti, Nurhikmah Dwi; Jaya, Amir; Mursalim, Mursalim (Journal of Teaching of English, 2021)
This study is aimed at determining the teachers’ purposes of using ICT and to provide information regarding the ICT applications used in teaching the English subject at SMA Negeri 4 Kendari. This study employed a descriptive design. To find out a clear understanding of this subject matter, the study focused on eight teachers who were teaching English using ICT-based learning. The data was collected by using a close-ended questionnaire with thirty items and interview with five questions, and analyzed by using SPSS 16.0 version. The result of this study showed that the teachers give their positive response to all item of the questionnaire. The teachers use ICT to help them for course and lesson planning, using ICT resources and assisted technology and using ICT to design teaching and learning unit plans and activities. Moreover, the teachers use the applications such as; Google Classroom, Moodle, Microsoft Teams, Quipper School, Edmodo and other media to support and link their teaching and learning process in the classroom. They also use HTML editor, Adobe Dreamweaver, Visual Studio Editor, etc. to support the students actively contribute their knowledge in the classroom practices. Therefore, this study can be concluded that the use of ICT in teaching the English subject is very important to support the teachers in providing their material, especially using some applications provided